Efficient Computation of Nonlinear Crest Distributions for Irregular Stokes Waves (Communications in Computational Physics, 2018)
This paper concerns the computation of nonlinear crest distributions for irregularStokes waves, and a numerical algorithm based on the Fast Fourier Transform(FFT) technique has been developed for carrying out the nonlinear computations. Inorder to further improve the computational efficiency, a new Transformed Rayleighprocedure is first proposed as another alternative for computing the nonlinear wavecrest height distributions, and the corresponding computer code has also been developed.In the proposed Transformed Rayleigh procedure, the transformation model ischosen to be a monotonic exponential function, calibrated such that the first three momentsof the transformed model match the moments of the true process. The numericalalgorithm based on the FFT technique and the proposed Transformed Rayleigh procedurehave been applied to calculating the wave crest distributions of a sea state with aBretschneider spectrum and a sea state with the surface elevation data measured at thePoseidon platform. It is demonstrated in these two cases that the numerical algorithmbased on the FFT technique and the proposed Transformed Rayleigh procedure canoffer better predictions than those from using the empirical wave crest distributionmodels. Meanwhile, it is found that our proposed Transformed Rayleigh procedurecan compute nonlinear crest distributions more than 25 times faster than the numericalalgorithm based on the FFT technique.